ANALYSIS OF COFFEE SHOP MARKETING STRATEGY OM BEWOK: ANALISIS STRATEGI PEMASARAN KEDAI KOPI OM BEWOK - Muhammad Ridwan; Hafidz Hanafiah (Yayasan Education and Social Center, 2021)
Along with the level of competition in the world of marketing, business people began to carry out their business strategies. One of them is marketing strategy which is overall business planning and strategy in turning prospective customers into customers. Coffee shop is a culinary business that is trending and loved by the community today. The emergence of several coffee shops both local shops and franchisecoffeeshops, did not discourage the business of this coffee shop increased. One of them is om bewok coffee shop located in Serang City. This research aims to analyze the marketing strategy of Om Bewok Coffee Shop. The research methods used are carried out qualitatively with analysis of 3C(Company, Competitor, Costumer), SWOT (Strength, Weakness, Opportunity, Threat), STP(Segmentation, Targeting, Positioning),and 4P (Price,Product, Place, Promotion). The results of the study concluded that Om Bewok Coffee Shop has carried out marketing strategies with consistent and commitment, in the future should be done the development of marketing strategies with digital technology adaptation